Advancing Quality Education in Architecture: A Comparative Study on Traditional and Digital Learning Approaches - Illaga, Lynne Ivy; Almaden, Antoniette; Ceniza, Nicole Grace; Francisco, Carla Nicole; Fuentes, Jezrael Philip; Santillan, Jeliane Marie; Tagbar, Trexie Margarette (JPAIR Multidisciplinary Research, 2026)
This study compares traditional and digital learning methods in developing design and visualization skills among fourth-year architecture students at a private higher education institution in Cebu City, Philippines. It focuses on four core competencies: accuracy, creativity, efficiency, and spatial understanding guided by Design Thinking, emphasizing empathy, ideation, and iterative problem-solving. The study explores how pedagogical strategies shape student outcomes. A quantitative comparative design was employed, involving 187 randomly selected students. Data were collected through a validated questionnaire and analyzed using descriptive statistics and paired t-test. Results showed that digital methods significantly enhanced accuracy and efficiency, especially in tasks requiring precision and technical output. Traditional methods, meanwhile, better support creative thinking and conceptual planning. Students reported that a blended approach combining both methods offered the most balanced and effective learning experience. The study concludes that a flexible, student-centered blended learning model best supports skill development in architectural education. This approach not only improves learning outcomes but also advances Sustainable Development Goal 4 by promoting inclusive, quality, and future-ready education. Furthermore, it aligns with internationalization by fostering digital fluency and pedagogical adaptability across diverse learning environments. The findings underscore the value of integrating thoughtful pedagogy with technology to prepare architecture students for the evolving demands of global design practice.